COVID-19 vaccine uptake and associated factors among pregnant women attending antenatal care in Debre Tabor public health institutions: A cross-sectional study - Chekol Abebe, Endeshaw; Ayalew Tiruneh, Gebrehiwot; Asmare Adela, Getachew; Mengie Ayele, Teklie; Tilahun Muche, Zelalem; Behaile T/Mariam, Awgichew; Tilahun Mulu, Anemut; Abebe Zewde, Edgeit; Dagnaw Baye, Nega; Asmamaw Dejenie, Tadesse (Frontiers in Public Health, 2022)
Background: Vaccination is the best means of reducing the increased risk of severe COVID 19 during pregnancy. Data on COVID 19 vaccine uptake among pregnant women in Ethiopia is scarce. Thus, this study aimed to assess COVID 19 vaccine uptake and associated factors among pregnant women. Method: An institution-based cross-sectional study was conducted among 634 pregnant women attending antenatal care in Debre Tabor public health institutions from March 14 to 30, 2022. Participants were recruited using a multistage sampling technique and data were collected via face-to-face interviews using a pre-tested structured questionnaire. Stata version 16.0 software was used for data analysis. Multiple logistic regression analysis was used to assess factors associated with COVID 19 vaccine uptake, with a p-value< 0.05 considered statistically significant. Result: Only 14.4% (95% CI: 11.7%-17.3%) of participants had received at least one dose of COVID-19 vaccines. The main reasons for declining vaccination were fear that the COVID 19 vaccine may have harmful side effects on the fetus or the mother. Being 45 or older (AOR: 1.75, 95%CI: 1.01–2.95), being married (AOR: 1.26, 95%CI: 1.12, 2.96), having good knowledge (AOR:3.52, 95%CI:1.83–3.87), and a positive attitude (AOR:4.81, 95% CI: 1.42–7.33) were positive predictors of COVID 19 vaccine uptake. But attaining a college or university education (AOR: 0.43, 95%CI: 0.12–0.69) was found to be a barrier to vaccine uptake by pregnant women. Conclusion: COVID 19 vaccination among pregnant women was substantially low. Old age, being married, low education, good knowledge, and a positive attitude were significant predictors of COVID-19 vaccine uptake. To enhance the COVID 19 vaccine uptake, the government should improve the knowledge and attitude of pregnant women toward the COVID 19 vaccine.